Environmental ethics in the education system for sustainable development of the Republic Belarus and the Russian Federation - Astabacyan, Tigran M. (Journal of the Belarusian State University. Ecology, 2020)
According to the 2018 Environmental Efficiency Index, Armenia ranks 63 among 180 countries. The biggest country challenges are air pollution, habitat protection (habitats), and the inefficient use of water resources. Adaptation to climate change is a priority of the Republic of Armenia. Currently, in accordance with the National Environmental Action Programme, the Republic of Armenia optimizes the use of natural resources and defines the overall country environmental policy.